Seed Rain of Selected Subsidence Basins in Karviná Region – Preliminary Results - PLOHÁK, Petr; ŠVEHLÁKOVÁ, Hana; RAJDUS, Tomáš; TURČOVÁ, Barbora (GeoScience Engineering, 2021)
Overall amount and quality of seeds reaching the area is an important factor in the development of plant communities in each habitat. It can be a significant source of diversity in anthropogenically disturbed areas. This study is focused on the survey of seed rain in habitats of waterlogged subsidence basins of the Karviná region, induced by deformations of overlying rocks in the area of deep coal mining. The density, species composition and dispersal strategies of captured seeds were monitored using funnel traps with a 35 cm diameter, fixed at a height of 0.5 m. A vegetation study was conducted to compare seed rain with above-ground vegetation using the Jaccard similarity index. Over 11 000 seeds of 27 plant species were captured in total. Seed rain was dominated by Salix alba species. Seed density varied significantly within individual sampling plots (7–12380 seeds/m2) with the average richness of four species. The diversity of above-ground vegetation was also low, with an average of 15 species per plot (100 m2). Similarity between seed rain and above-ground vegetation of subsidence basins is 27.6 % and 52 % within the woody species community. It is evident that the seed rain of waterlogged subsidence basins contains species of floodplain forests and wetland vegetation. On the other hand, invasive and expansive species identified both in seed rain and above-ground vegetation can potentially endanger the development of the succession of these habitats. The analysis of seed dispersal also shows a significant proportion of species of arid and mesic habitats. Keywords: Dispersal strategy; Karviná; Seed rain; Subsidence basin.